Leadership, Culture and Sustainable Built Environment. - Kumaraswamy, Mohan (Built Environment Project and Asset Management: Volume 5, Issue 2., 2015)
This e-book on 'Leadership, Culture and Sustainable Built Environment' examines the important link between leadership, culture and sustainability which have separately been the subject of numerous studies in a built environment context. After a rigorous double blind review process, six papers have been selected for publication in this e-book that brings these separate issues together; with one paper on sustainability in the built environment, three papers on the link between leadership and sustainability in the built environment and two papers on the contribution of culture in a sustainable bu.